ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND SWITCHING TERHADAP PENGGUNAAN E-WALLET - Sarah Michelle Lydia Hutauruk (2021)
Competition in the digital world, especially in e-wallets, is now growing. Every year there are many special offers offered by each e-wallet to attract public interest. This allows people to move from e-wallet one to e-wallet GoPay. This study aims to analyze and determine the effect of looking for variations, promotions, and consumer dissatisfaction with the shift in e-wallet brands. The object of this research is the GoPay e-wallet. The sample in this study were 75 respondents using the purposive sampling technique because it has several criteria for respondents. Hypothesis testing in this study uses the inner model analysis, outer model, and t-statistical test using the SmartPLS 3.0 analysis tool and a significance level of 5% (0.05). The test results of this study resulted in an R-Square value of 0.709 or 70.9%, and the rest of 29.1% was influenced by other independent variables, such as product attributes, lifestyle, product quality, and price. Thus it can be concluded that looking for variations does not have a significant effect on brand movement, the promotion has a significant effect on brand shift, and consumer dissatisfaction has a significant effect on brand switching.